Deep Learning for Additive Screening in Perovskite Light‐Emitting Diodes. Issue 37 (3rd August 2022) - Zhang, Liang; Li, Na; Liu, Dawei; Tao, Guanhong; Xu, Weidong; Li, Mengmeng; Chu, Ying; Cao, Chensi; Lu, Feiyue; Hao, Chenjie; Zhang, Ju; Cao, Yu; et al.
Abstract: Additive engineering with organic molecules is of critical importance for achieving high‐performance perovskite optoelectronic devices. However, experimentally finding suitable additives is costly and time consuming, while conventional machine learning (ML) is difficult to predict accurately due to the limited experimental data available in this relatively new field. Here, we demonstrate a deep learning method that can predict the effectiveness of additives in perovskite light‐emitting diodes (PeLEDs) with a high accuracy up to 96 % by using a small dataset of 132 molecules. This model can maximize the information of the molecules and significantly mitigate the duplicated problem that usually happened with previous models in ML for molecular screening. Very high efficiency PeLEDs with a peak external quantum efficiency up to 22.7 % can be achieved by using the predicated additive. Our work opens a new avenue for further boosting the performance of perovskite optoelectronic devices. Abstract : Additive engineering has significantly improved the performance of perovskite optoelectronic devices, and is promising for further enhancing perovskite devices' efficiency. A key challenge is to choose suitable additive for perovskite. The approach based on deep learning helps to predict the suitable additives, giving rising to high‐performance near‐infrared perovskite light‐emitting diodes.